Allelopathic potential of radish (Raphanus sativus L.) on germination and seedling growth of some plants species. - Solaf H. Rahman; Saman A. Rasul (Zanco Journal of Pure and Applied Sciences, 2023)
The purpose of this study was to determine the allelopathic activity of shoot and root aqueous extracts of radish (Raphanus sativus L.) on germination and seedling growth of bread wheat (Triticum aesitivum L.), barley (Hordeum vulgare), wild barley (Hordeum spontaneum L.), and wild oat (Avena fatua L.). The concentration was used in this study were (0%, 15%, 30%, 45%, and 60%). The experiment was conducted in a sterilized Petri dish for 10 days at 22 °C, with the experimental units arranged in a randomized complete design. In general, the study's findings revealed the significant effects of concentration levels (15%, 30%, 45%, 60% compared to control treatments. The concentration 40% and 60% were completely inhibiting the seedling germination and growth while the lowest concentration 15% had the least negative effect on seedling growth and germination. Aqueous extract of shoot radish was more effective on seed germination than root of radish. So, all results recommended that the aqueous extract of shoot and root of radish may act as a bioherbicide to inhibit germination and seedling growth.